2021
DOI: 10.1038/s41598-021-82428-5
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the sensitivity and specificity of anti-SARS-CoV-2 IgM and IgG antibodies for symptomatic COVID-19 in Japan

Abstract: The accurate and prompt diagnosis of SARS-CoV-2 infection is required for the control and treatment of the coronavirus infection disease 2019 (COVID-19). In this study, we aimed to investigate the time courses of the anti-severe acute corona respiratory syndrome coronavirus 2 (SARS-CoV-2) IgM and IgG titers and to evaluate the sensitivity and specificity of such tests according to the specific day after the onset of COVID-19 among a patient population in Japan. We measured the titers of SARS-CoV-2 IgM and IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 28 publications
1
43
5
Order By: Relevance
“…According to the manufacturer's instructions, ≥10 arbitrary units (AU)/mL is considered positive. The sensitivity of the iFlash-SARS-CoV-2 IgG kit is 63.6% for RT-PCR-positive patients 9 to 10 days after symptom onset and 100% for RT-PCR-positive patients ≥15 days after symptom onset, whereas the specificity of the kit is 100% for samples from RT-PCR-negative patients 11 . Parai et al reported sensitivity and specificity values of 76.9% and 100%, respectively, for the iFlash-SARS-CoV-2 IgG kit 12 .…”
Section: Measurement Of Anti-sars-cov-2 Antibody Levelsmentioning
confidence: 97%
“…According to the manufacturer's instructions, ≥10 arbitrary units (AU)/mL is considered positive. The sensitivity of the iFlash-SARS-CoV-2 IgG kit is 63.6% for RT-PCR-positive patients 9 to 10 days after symptom onset and 100% for RT-PCR-positive patients ≥15 days after symptom onset, whereas the specificity of the kit is 100% for samples from RT-PCR-negative patients 11 . Parai et al reported sensitivity and specificity values of 76.9% and 100%, respectively, for the iFlash-SARS-CoV-2 IgG kit 12 .…”
Section: Measurement Of Anti-sars-cov-2 Antibody Levelsmentioning
confidence: 97%
“…Therefore, IgG is commonly used to indicate past infection. [ 7 , 8 ] Despite researches showed that IgG may persist for months, [ 8 , 9 ] there are still no studies claiming about permanent immunity [ 10 ] mostly because of the novelty of the COVID‐19. In addition, a positive correlation can be found between the antibody levels and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the significant differences in the present study are among values below the cutoffs, and there was some discrepancy in the results. On the other hand, there are some reports suggesting the higher or lower cutoff value [15,29,30], and the cutoff value itself for this emerging infectious disease is still under the validation process especially in asymptomatic subjects, which might be changed in future. Further study is needed to confirm the quantitative meanings of these values.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al analyzed the antibody titers of Japanese patients with symptomatic COVID-19, and suggested that the cutoff values in Japan might be lower than the manufacturer's reported cutoff [15]. Using the cutoff value of 5AU/mL, the number of positive participants for IgM was 42 (0.64%), and one for IgG was 70 (1.06%).…”
Section: Participants With Elevated Igg and Igm Titersmentioning
confidence: 99%